2023
DOI: 10.1038/s41398-023-02307-7
|View full text |Cite
|
Sign up to set email alerts
|

Fecal microbiota transplantation improves VPA-induced ASD mice by modulating the serotonergic and glutamatergic synapse signaling pathways

Abstract: Autism spectrum disorder (ASD) is a complex behavioral disorder diagnosed by social interaction difficulties, restricted verbal communication, and repetitive behaviors. Fecal microbiota transplantation (FMT) is a safe and efficient strategy to adjust gut microbiota dysbiosis and improve ASD-related behavioral symptoms, but its regulatory mechanism is unknown. The impact of the microbiota and its functions on ASD development is urgently being investigated to develop new therapeutic strategies for ASD. We recons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…These observations align with prior studies of fecal microbiome analyses in autistic children, albeit with some nuances. For example, Turicibacter has been implicated in ASD-related behaviors, as demonstrated by symptom improvement in VPA mouse models following fecal microbiota transplantation ( Wang J. et al, 2023 ). Additionally, research has shown an inverse correlation between Turicibacter abundance and sex hormones, potentially offering insights into the prevalence of ASD in females ( Wu et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…These observations align with prior studies of fecal microbiome analyses in autistic children, albeit with some nuances. For example, Turicibacter has been implicated in ASD-related behaviors, as demonstrated by symptom improvement in VPA mouse models following fecal microbiota transplantation ( Wang J. et al, 2023 ). Additionally, research has shown an inverse correlation between Turicibacter abundance and sex hormones, potentially offering insights into the prevalence of ASD in females ( Wu et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…It has also been proposed as a safe and effective strategy to modulate the symbiosis of the gastrointestinal microbiota and improve behavioral symptoms in children with ASD 440,441 . Recently, a study showed that FMT improved VPA‐induced ASD mice by modulating 5‐hydroxytryptaminergic and glutamatergic synaptic signaling pathways 442 . Modified FMT therapy for children with ASD resulted in significant improvements in gastrointestinal symptoms and ASD symptoms, and follow‐up of these individuals after 2 years showed that most of the improvements in gastrointestinal symptoms were maintained, including significant increases in bacterial diversity and relative abundance of beneficial bacteria such as bifidobacterial 440,443 .…”
Section: Methods Of Educational Interventionmentioning
confidence: 99%
“…440,441 Recently, a study showed that FMT improved VPA-induced ASD mice by modulating 5-hydroxytryptaminergic and glutamatergic synaptic signaling pathways. 442 Modified FMT therapy for children with ASD resulted in significant improvements in gastrointestinal symptoms and ASD symptoms, and follow-up of these individuals after 2 years showed that most of the improvements in gastrointestinal symptoms were maintained, including significant increases in bacterial diversity and relative abundance of beneficial bacteria such as bifidobacterial. 440,443 However, due to the complexity of the intestinal microbiota, FMT therapies are still highly heterogeneous with respect to donor selection, material preparation, ideal dosing regimen, and cost-effectiveness, and are still a long way from clinical application.…”
Section: Interventions For Asd Targeting the Microbiota-gut-brain Axismentioning
confidence: 95%
“…It is a new strategy to treat diseases related to microbial imbalance by regulating intestinal flora (Figure 5). FMT has been shown to be effective in the treatment of type 2 diabetes mellitus, neurodegenerative diseases, autism spectrum disorder and so on (Wu et al, 2022;Matheson and Holsinger, 2023;Wang et al, 2023). FMT improved the irradiated animal survival rate, increased peripheral blood leukocyte count, and intestinal epithelial integrity, improved the gastrointestinal function, which can safely and effectively improve the symptoms of chronic radiation enteritis patients with intestinal and mucosa damage.…”
Section: Microbial Therapy Of Radiation Enteritismentioning
confidence: 99%